2018
DOI: 10.1038/s41598-018-31696-9
|View full text |Cite
|
Sign up to set email alerts
|

Groucho related gene 5 (GRG5) is involved in embryonic and neural stem cell state decisions

Abstract: Groucho related gene 5 (GRG5) is a multifunctional protein that has been implicated in late embryonic and postnatal mouse development. Here, we describe a previously unknown role of GRG5 in early developmental stages by analyzing its function in stem cell fate decisions. By both loss and gain of function approaches we demonstrate that ablation of GRG5 deregulates the Embryonic Stem Cell (ESC) pluripotent state whereas its overexpression leads to enhanced self-renewal and acquisition of cancer cell-like propert… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 73 publications
(68 reference statements)
1
9
0
Order By: Relevance
“…5K; Fisher's exact test P value = 7.3e-08; log-rank test P value = 0.031). Notably, given that AES suppresses WNT signaling 70,71 , our analysis in this part strengthened the link of WNT signaling to the stratification and clinical outcome of MMASs. Finally, upon further examination, we noticed that some MMAS-1 patient samples exhibit upregulated CMS1 signature pathways (inflammatory response and interferon response) and CMS4 signature pathways (angiogenesis, EMT, extracellular matrix mCRC, and TGF-β up) 36 .…”
Section: Characterization Of Nmf-assigned Subtypes Shows Differentialsupporting
confidence: 55%
“…5K; Fisher's exact test P value = 7.3e-08; log-rank test P value = 0.031). Notably, given that AES suppresses WNT signaling 70,71 , our analysis in this part strengthened the link of WNT signaling to the stratification and clinical outcome of MMASs. Finally, upon further examination, we noticed that some MMAS-1 patient samples exhibit upregulated CMS1 signature pathways (inflammatory response and interferon response) and CMS4 signature pathways (angiogenesis, EMT, extracellular matrix mCRC, and TGF-β up) 36 .…”
Section: Characterization Of Nmf-assigned Subtypes Shows Differentialsupporting
confidence: 55%
“…AES could inhibit the Notch pathway through blocking the Notch signaling transcription complex composed of the NOTCH intracellular domain (NICD), the transcription factor RBPJ, and the cofactor MAML 11 . AES also inhibited HIF1α-mediated transcription as well as AR and BMP signaling 13 , 14 , 48 . Furthermore, AES has been shown to inhibit the Wnt/β-catenin signaling cascade through interacting with TCF4 and disrupting β-catenin and TCF4 binding 12 .…”
Section: Discussionmentioning
confidence: 92%
“…Amino-terminal enhancer of split (AES), a member of the Groucho/transducin-like enhancer of split/Grorelated gene (Gro/TLE/Grg) family of transcriptional co-repressors, has been identified as a metastasis suppressor for CRC 11 . Previous studies showed that AES could inhibit several signaling pathways, including the Notch pathway, the Wnt/β-catenin pathway, the Androgen Receptor (AR) and Bone Morphogenetic Protein (BMP) signaling pathways 11 - 14 . These studies indicate that AES may exert its suppressive effect on CRC metastasis through mediating the multiple pathways.…”
Section: Introductionmentioning
confidence: 99%
“…Additional references: (Bain et al., 1995; Chanoumidou et al., 2018; Eiraku & Sasai, 2011; Forouzanfar et al., 2015; Rao et al., 2020). …”
Section: Neural Induction From Mammalian Es Cellsmentioning
confidence: 99%